Institutional model for integrating Sasi and local wisdom into Indonesia's national mangrove conservation policy - ENO SUWARNO; IRWAN EFFENDI; JENNY KOCE MATITAPUTTY; ZAINURI ZAINURI; DODI SUKMA RA (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Suwarno E, Effendi I, Matitaputty JK, Zainuri, RA DS. 2026. Institutional model for integrating Sasi and local wisdom into Indonesia's national mangrove conservation policy. Biodiversitas 27 (4): d270409. https://doi.org/10.13057/biodiv/d270409. Indonesia's ambitious mangrove conservation targets face a persistent challenge in substantively integrating local governance systems like Sasi. This study employs a qualitative regulatory gap analysis of three document corpora: national legal instruments, ethnographic studies on Sasi, and supporting academic literature. We identify fundamental tensions between Maluku's temporally-based Sasi system and Indonesia's spatial zoning-based national mangrove policy, particularly regarding the non-recognition of traditional kewang authority and incompatibility between temporal moratoriums (Sasi tutup) and static spatial zoning. Complementary potential exists in monitoring and enforcement capacities. To bridge this gap, we propose the Temporal-Spatial Bridge (TSB) model, a hybrid institutional framework with four pillars: mutual legal recognition, nested temporal-spatial rules, tiered polycentric enforcement, and localized benefit-sharing. The model is presented as a conceptual hypothesis requiring empirical testing, not as a ready-to-implement policy framework. It offers potential to enhance biodiversity outcomes by embedding life-cycle protection into national planning and formalizing local ecological knowledge into adaptive management systems. We conclude that bridging legal pluralism in conservation requires deliberate institutional engineering, offering the TSB model as a conceptual template derived from the Maluku context for Indonesia and similar contexts.